(untitled) (Slavic Studies, 2024)
When translating foreign works there often arises a need for new words, in order to convey the elements of one culture into another. The phenomenon of borrowing words directly from the original language destroys the tendency for a language to develop itself. On the other hand, coining new words that correspond to our own language continuously adds to and enriches our vocabulary. A translation not only has to observe the meaning of a word, but it also has to take into consideration the context of its usage and its evolution within the language, as well.